Spectral Streams of Post-Consciousness in Mike McCormack’s Solar Bones (2016) - Asier Altuna-García de Salazar (Universidad de Valladolid, 2021)
This article analyses Mike McCormack’s novel Solar Bones (2016) which narrates in a run-on sentence Marcus Conway’s everyday life within the rural context of a 2008 Celtic Tiger Ireland about to collapse. Drawing upon the narratological precepts of experimental writing, especially the use of streams of consciousness, and Derrida’s hauntology, this article argues that McCormack’s novel charts tensions of coherence and collapse in post-Celtic Tiger fiction. The narration takes place within a post- perspective as Marcus’s ghost brings it into existence. The experimentation with streams of post-consciousness and spectrality provides McCormack with valid aesthetic mechanisms to respond in fiction to Celtic Tiger concerns.